Lactobacillus fermentum CECT5716 Alleviates the Inflammatory Response in Asthma by Regulating TLR2/TLR4 Expression - Wang, Weifang; Li, Yunfeng; Han, Guojing; Li, Aimin; Kong, Xiaomei (Frontiers in Nutrition, 2022)
Abstract Background: Asthma is a chronic disease, which is harmful to the health of the body and the quality of life. Supplementation of Lactobacillus can affect the immune environment of the lungs through the gut-lung axis. This study aimed to explore the potential regulatory targets of Lactobacillus to relieve inflammation in asthma and determine a new approach for improving asthma. Methods: A mouse ovalbumin (OVA)-induced model was constructed. OVA mice were supplemented with Lactobacillus fermentum CECT5716 by gavage. The gut microbiota composition of normal and OVA mice was analyzed using 16S ribosomal DNA identification. BALF, serum, lung tissues, and duodenal tissues were collected. Wright’s staining was performed to determine the cell content of the alveolar lavage fluid. Hematoxylin-eosin staining, Masson staining, and periodic acid-Schiff staining were performed to observe the improvement in the lungs of OVA mice supplemented with Lactobacillus. Immunofluorescence was performed to measure the severity of the intestinal barrier leakage. Enzyme-linked immunosorbent assay was carried out to determine the expression levels of inflammatory cell factors, while quantitative reverse transcription-polymerase chain reaction and western blotting were performed to detect the levels of toll-like receptor 2 (TLR2)/TLR4 expression and cell adhesion factors. Results: Compared with Control mice, OVA mice exhibited malignant conditions, such as intestinal leakage and lung edema. After supplementation with Lactobacillus, the inflammatory cell content in the bronchoalveolar lavage fluid decreased, and the inflammatory response was alleviated. The level of TLR2/TLR4 expression was reduced. The inflammatory cell infiltration in the airway mucosa of OVA mice was improved, alveolar swelling was reduced and the basement membrane appeared thinner. Conclusion: The Lactobacillus inhibited the TLR2/TLR4 expression in OVA mice. Supplementation with Lactobacillus can alleviate the inflammatory response in OVA mice, inhibit pulmonary fibrosis, and treat asthma.